The Effect of Innovation on the Performance of State Civil Apparatus at the Education and Culture Office - Devina Ersandy; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2021)
In everyday life, we often hear the word Innovation. Innovation appears in the organization was first introduced by Schumpeter in 1934. Innovation is very important in organizations to increase the productivity of agencies. Innovation itself is an idea that is applied, and has a scientific basis. Underlying this research is that in fact there are still several factors that cause performance to be not optimal. The purpose of this research is to prove the effect of innovation on the performance of the State Civil Apparatus at the Education and Culture Office of Sidoarjo. This study uses quantitative methods and data collection techniques using interviews and questionnaires. Sampling used the total population of the State Civil Apparatus of the Education and Culture Office of Sidoarjo, namely 57 employees. The results of this study indicate that innovation has an influence on the performance of the State Civil Apparatus at the Education and Culture Office of Sidoarjo. Keywords – Innovation, employee performance.